The role of smart cities in promoting health - Abdelrhman Mohammed ELHASSAN AHMED (Social Empowerment Journal, 2024)
We aim through this study to identify the role of smart cities in promoting health through a descriptive study, by studying the relationship between smart cities and their promotion of health within the urban environment, using smart city technologies to create more efficient healthcare systems, and identifying smart digital solutions to monitor epidemics and diseases, and environmental health, to enhance the health of its residents. To achieve the objectives of the study and answer its questions, and based on the nature of the study topic, we relied on a set of sources to collect scientific material. Our study reached a number of results, the most important of which are: Smart cities contribute to promoting health by providing innovative and advanced health services, using technologies that contribute to creating more efficient health care systems. And including digital technology in the solutions provided for health care. The study recommended the importance of adopting smart cities, providing smart infrastructure in cities, and providing advanced technological infrastructure that facilitates access to health services faster and more efficiently.